PENGUNAAN ENDAPAN AIR GAMBUT SEBAGAI AMELIORAN ALTERNATIF TERHADAP BEBERAPA SIFAT KIMIA ULTISOL DAN HASIL TANAMAN JAGUNG SEMI (Zea mays L ) - Teguh Budi Prasetyo; Husnita Husnita; Irwan Darfis (Jurnal Solum, 2008)
The main problems of Ultisols are high Al concentration, low pH, low cation exchangeable capacity (CEC), and low fertility.  The objectives of this reasearch were to study the effect of peat water deposit to some chemical properties of Ultisols and to determine the optimal level of peat water deposit for optimum corn yield.  The experimental design was the complete randomized design that consisted of 5 levels of peat water deposit (0, 800, 1600, 2400, and 3200 kg/ha).  The results showed that the application of peat water deposit could reduce exchangeable Al, increase CEC and soil P concentration, P-uptake, and corn yield.  The highest corn yield was obtained at application of 3200 kg peat water deposit /ha.Key Words : Ultisols, peat water precipitation, soil chemical characteristics, corn